Avaliação de atributos de solos sob diferentes usos em perímetro irrigado do Vale do Rio São Francisco - CORRÊA, Rossini Mattos (2007)
The Brazilian northeast semi-arid region finds in the irrigated agriculture income and job. There is a big amount of lands that can be irrigated but the knowledge of the irrigated agroecosystems in the semi-arid region is still incipient, thus studies are necessary to ensure a bigger success of these agribusinesses. This work aimed to evaluate and to compare the attributes of the soil under different uses and management in an irrigated perimeter in the northeast of Brazil and to compare different uses and management of the soil. In the irrigated perimeter Ico-Mandantes, situated in the cities of Petrolândia and Floresta, in Pernambuco semi arid, the populations were separated by their uses and managements in annual crops (C), fruticulture (F), discarded lands (D), pasture (P), native vegetation (V). Undisturbed and disturbed soil samples were collected, in layers of 0-10, 10-30 and 30-60 cm, for physical and chemical analysis. The indications were submitted to multivariate analysis, by Principal Component Analysis, and clustering by the Tocher method. A soil quality index was built using the Principal Component Analysis. The results showed that the classification of the estratos was relative, it had not being observed attribute that restricted the development of a good soil quality, excepted for the estrato D where the soil depth was restrictive. Alterations in physical and chemical attributes were observed in all the layers, the chemical alterations were bigger, it was observed because estrato V stayed alone in the clustering analysis in all the layers. The chemical attributes had stronger participation in the joint analysis of the physical and chemical attributes. In general, the three layers in the estratos C, P and D had presented the best chemical soil quality. The soil physical quality was better in the estratos F and P in relation to estrato C in the layers of 0-10 and 10-30 cm, possibly in order of the less intense soil management in the estratos F and P. The alterations observed show the need of monitoring the attributes of soil incorporated in productive systems under irrigation in the semi arid in the way of get information of the evolution of the values of these attributes to adopt control solutions, if had any need, mainly in estratos C and D that presented greater physical and chemical modifications.